2011
DOI: 10.1111/j.1365-3040.2011.02399.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to insect herbivory: interactions between photosynthesis, reactive oxygen species and hormonal signalling pathways

Abstract: Under herbivore attack plants mount a defence response characterized by the accumulation of secondary metabolites and inhibitory proteins. Significant changes are observed in the transcriptional profiles of genes encoding enzymes of primary metabolism. Such changes have often been interpreted in terms of a requirement for an increased investment of resources to 'fuel' the synthesis of secondary metabolites. While enhanced secondary metabolism undoubtedly exerts an influence on primary metabolism, accumulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
184
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(218 citation statements)
references
References 101 publications
15
184
1
4
Order By: Relevance
“…There was a significant down regulation of the carbohydrate metabolites noted in the DT cultivars as compared to the DS cultivars (Figure 7). The photosynthetic pathway is the most affected when plants are subjected to abiotic stresses such as drought (Kerchev et al, 2012). This negatively impacts on primary metabolism, affecting metabolites such as sugars, sugar alcohols and amino acids.…”
Section: Carbohydrates Metabolismmentioning
confidence: 99%
“…There was a significant down regulation of the carbohydrate metabolites noted in the DT cultivars as compared to the DS cultivars (Figure 7). The photosynthetic pathway is the most affected when plants are subjected to abiotic stresses such as drought (Kerchev et al, 2012). This negatively impacts on primary metabolism, affecting metabolites such as sugars, sugar alcohols and amino acids.…”
Section: Carbohydrates Metabolismmentioning
confidence: 99%
“…In our study, we found that the feeding of herbivores on S. lapponum leaves induced accumulation of H 2 O 2 very close to the area of damage. Similarly, other studies have provided direct evidence for H 2 O 2 accumulation following plant infestation by either chewing or piercing-sucking insects (Kerchev et al, 2012, and references therein). For example, a study concerning infestation of lima bean by the chewing caterpillar Spodoptera littoralis Boisd.…”
Section: Discussionmentioning
confidence: 66%
“…The magnitude of the insect herbivory effect on photosynthetic capacity is multifaceted, depending mostly on the type of feeding habits and the specificity of plant defense responses (Nabity et al, 2009). It has been found that plant genotypes that are capable to maintain photosynthesis under insect attack often exhibit greater resistance, which supports the hypothesis that insect-induced changes in photosynthesis are genetically programmed (Kerchev et al, 2012). In general, healthy plants have photosynthetic efficiency (F v /F m ) of 0.8-0.9, while plants suffering from stress have ratios of ca.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations